A role for XRCC2 gene polymorphisms in breast cancer risk and survival. Issue 7 (31st May 2011) - Lin, Wei-Yu; Camp, Nicola J; Cannon-Albright, Lisa A; Allen-Brady, Kristina; Balasubramanian, Sabapathy; Reed, Malcolm W R; Hopper, John L; Apicella, Carmel; Giles, Graham G; Southey, Melissa C; Milne, Roger L; Arias-Pérez, Jose I; et al.
Abstract : Background: The XRCC2 gene is a key mediator in the homologous recombination repair of DNA double strand breaks. It is hypothesised that inherited variants in the XRCC2 gene might also affect susceptibility to, and survival from, breast cancer. Methods: The study genotyped 12 XRCC2 tagging single nucleotide polymorphisms (SNPs) in 1131 breast cancer cases and 1148 controls from the Sheffield Breast Cancer Study (SBCS), and examined their associations with breast cancer risk and survival by estimating ORs and HRs, and their corresponding 95% CIs. Positive findings were further investigated in 860 cases and 869 controls from the Utah Breast Cancer Study (UBCS) and jointly analysed together with available published data for breast cancer risk. The survival findings were further confirmed in studies (8074 cases) from the Breast Cancer Association Consortium (BCAC). Results: The most significant association with breast cancer risk in the SBCS dataset was the XRCC2 rs3218408 SNP (recessive model p=2.3×10 −4, minor allele frequency (MAF)=0.23). This SNP yielded an ORrec of 1.64 (95% CI 1.25 to 2.16) in a two-site analysis of SBCS and UBCS, and a meta-ORrec of 1.33 (95% CI 1.12 to 1.57) when all published data were included. This SNP may mark a rare risk haplotype carried by two in 1000 of the control population. Furthermore, the XRCC2 coding R188H SNP (rs3218536, MAF=0.08) was significantly associated with poor survival, with an increased per-allele HR of 1.58 (95% CI 1.01 to 2.49) in a multivariate analysis. This effect was still evident in a pooled meta-analysis of 8781 breast cancer patients from the BCAC (HR 1.19, 95% CI 1.05 to 1.36; p=0.01). Conclusions: These findings suggest that XRCC2 SNPs may influence breast cancer risk and survival.